2006
DOI: 10.1080/10934520600867854
|View full text |Cite
|
Sign up to set email alerts
|

Multipathway Polycyclic Aromatic Hydrocarbon and Pyrene Exposure Among Children Living in Campania (Italy)

Abstract: Multipathway exposure to polycyclic aromatic hydrocarbons (PAHs) and Pyrene (Py) was studied among children ages 7-9 living in two areas of the Campania Region (South-Italy) classified as urban and rural. During five consecutive days PAHs and Py were detected in air samples from outdoors, indoors (school and home), individuals at inhalatory levels, and in food and beverages (defined as food) consumed daily by each child. 1-hydroxypyrene (1-OHP) was detected in children's urine. Gender, weight and height of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 41 publications
2
16
1
Order By: Relevance
“…Overall, concentration levels of outdoor particulate PAHs were similar to those reported in earlier studies (Castro et al, 2011;Slezakova et al, 2013a,b). The levels registered in ambient air of the selected preschool were much higher compared to other Portuguese and Italian cities (Alves et al, 2014;Cirillo et al, 2006). On the contrary, in close proximity of schools situated in Asian countries authors reported much higher concentrations of particle-bound PAHs (Jyethi et al, 2014;Ruchirawat et al, 2006Ruchirawat et al, , 2007 compared to this study.…”
Section: Outdoor Pahs and Source Identificationcontrasting
confidence: 86%
“…Overall, concentration levels of outdoor particulate PAHs were similar to those reported in earlier studies (Castro et al, 2011;Slezakova et al, 2013a,b). The levels registered in ambient air of the selected preschool were much higher compared to other Portuguese and Italian cities (Alves et al, 2014;Cirillo et al, 2006). On the contrary, in close proximity of schools situated in Asian countries authors reported much higher concentrations of particle-bound PAHs (Jyethi et al, 2014;Ruchirawat et al, 2006Ruchirawat et al, , 2007 compared to this study.…”
Section: Outdoor Pahs and Source Identificationcontrasting
confidence: 86%
“…Analyzing the same 15 PAHs, Krugly et al (2014) found much higher levels of PM 2.5 -bound PAHs (20.1-131 ng m −3 )in indoor air of schools in Lithuania. With the exception to S2, the indoor levels in schools of this study (Σ PAHs 2.8-20 ng m −3 ) were rather similar to schools in Rome (1.6-16 ng m −3 ) (Cirillo et al, 2006). Romagnoli et al (2014) also found PM 2.5 -bound PAHs in similar ranges (1.8-8.3 ng m −3 ) in indoor air of schools (sampled during winter season).…”
Section: S1supporting
confidence: 70%
“…Data available for primary schools (i.e. children 6-11yearsold)comefromafew European studies (Alves et al, 2014;Carpente and Bushkin-Bedient, 2013;Cirillo et al, 2006;Jovanović et al, 2014;Krugly et al, 2014;Moshammer and Neuberger, 2003;Romagnoli et al, 2014), Asia (Jyethi et al, 2014;Ruchirawat et al, 2006Ruchirawat et al, , 2007Tuntawiroon et al, 2007) and USA (Eiguren-Fernandez et al, 2007). However, the majority of those were typically conducted in a limited number of schools (typically 1-2 schools; only two known studies used a greater number of schools, namely 5 and 6; Krugly et al, 2014;Romagnoli et al, 2014), often situated just in one/same type of environment.…”
Section: Introductionmentioning
confidence: 99%
“…Available literature reports that food is the main source of human's exposure to PAHs (Cirillo et al, 2006;Garcia-Falcón et al, 2003;Ibanez et al, 2005;White, Fernandes, & Rose, 2008). Contamination of agricultural products as well as plant-origin foodstuffs is a consequence of the natural environment's contamination (Camargo & Toledo, 2003;Jánská, Hajšlová, Tomaniová, Kocourek, & Vávrová, 2006;Mo, Cai, Tang, Zeng, & Wu, 2009).…”
Section: Introductionmentioning
confidence: 97%